2007
DOI: 10.1002/chem.200600679
|View full text |Cite
|
Sign up to set email alerts
|

Oxo‐ and Imidovanadium Complexes Incorporating Methylene‐ and Dimethyleneoxa‐Bridged Calix[3]‐ and ‐[4]arenes: Synthesis, Structures and Ethylene Polymerisation Catalysis

Abstract: Reaction of [V(X)(OR)3] (X=O, Np-tolyl; R=Et, nPr or tBu) with p-tert-butylhexahomotrioxacalix[3]areneH3, LH3, affords the air-stable complexes [{V(X)L}n] (X=O, n=1 (1); X=Np-tolyl, n=2 (2)). Alternatively, 1 is readily available either from interaction of [V(mes)3THF] with LH3, and subsequent oxidation with O2 or upon reaction of LLi3 with [VOCl3]. Reaction of [V(Np-tolyl)(OtBu)3] with 1,3-dimethylether-p-tert-butylcalix[4]areneH2, Cax(OMe)2(OH)2, afforded [{VO(OtBu)}2(mu-O)Cax(OMe)2(O)2].2 MeCN (42 MeCN), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
97
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 82 publications
7
97
1
1
Order By: Relevance
“…for these systems that the presence of the oxygen bridge in the macrocycle can help to stabilize the catalytically-active species, a situation reminiscent of the vanadium-based calixarene polymerization catalysis of ethylene [31]. When these systems were employed for the ROP of rac-lactide, best conversions were achieved at 110 °C with the ratio 100:1:1 (rac-LA:Al:BnOH) over 12 h. For organoaluminium systems, the ROP of lactide often requires more robust conditions than those employed for ε-CL [32].…”
Section: Organoaluminium Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…for these systems that the presence of the oxygen bridge in the macrocycle can help to stabilize the catalytically-active species, a situation reminiscent of the vanadium-based calixarene polymerization catalysis of ethylene [31]. When these systems were employed for the ROP of rac-lactide, best conversions were achieved at 110 °C with the ratio 100:1:1 (rac-LA:Al:BnOH) over 12 h. For organoaluminium systems, the ROP of lactide often requires more robust conditions than those employed for ε-CL [32].…”
Section: Organoaluminium Complexesmentioning
confidence: 99%
“…Furthermore, the systems 27 and 29 exhibit an induction period that, following a 15%-20% Scheme 7. Zinc complexes (27)(28)(29)(30)(31)(32).…”
Section: Use Of Iihmentioning
confidence: 99%
“…Under the same catalytic conditions, vanadyl complexes bearing methylene-bridged (-CH 2 -) calix [4]arenes proved to have far inferior activities, though still far better than those observed previously for calix [4]arene-based systems. [3] Herein, we extend these studies to the other Group 5 metals, niobium and tantalum, and report the synthesis, characterisation and ethylene polymerisation behaviour of calix[n]arenes (n = 4, 6 and 8), and compare this behaviour with that of related oxacalix [3]arene complexes. Metallocalix[n]arenes incorporating niobium or tantalum are rather rare, with reports restricted to the calix [4]arene work of Floriani and co-workers [4] and more recently Radius and co-workers.…”
mentioning
confidence: 95%
“…[2] However, recently we have found that vanadyl complexes bearing dimethyleneoxa-bridged (-CH 2 OCH 2 -) oxacalix [3]arenes form extremely active catalytic species upon interaction with dimethylaluminium chloride (DMAC) in the presence of the re-activator ethyl trichloroacetate (ETA). Under the same catalytic conditions, vanadyl complexes bearing methylene-bridged (-CH 2 -) calix [4]arenes proved to have far inferior activities, though still far better than those observed previously for calix [4]arene-based systems.…”
mentioning
confidence: 99%
“…Moreover, we prepared the adamantylimido complexes containing 2-or 8-(anilidomethyl)-quinoline ligands, V(NAd)Cl 2 [(2,6-Me 2 C 6 H 3 )NCH 2 (C 9 H 6 N)] (2a,3a, Scheme 2), and V(N-2-MeC 6 H 4 )Cl 2 [2-ArNCH 2 (C 5 H 4 N)] complexes (4a,b) and explored reactions with ethylene in the presence of MAO (Table 1) [17]: remarkable effect of the imido ligand toward the selectivity (oligomer, polymer) was observed in the presence of MAO (Table 1, runs 9-12), whereas the reaction products by the quinoline analogues were a mixture of PE and oligomers. Since the reaction products by 1a,b in presence of Et 2 AlCl or Me 2 AlCl were PE, in this paper, we thus explored reactions with ethylene in the presence of halogenated Al alkyls to confirm our hypothesis outlined in Scheme 1, for example in ethylene polymerization by the other vanadium complex catalysts, [18][19][20][21][22][23][24]. Scheme 2.…”
Section: Introductionmentioning
confidence: 90%